Opportunities and Pitfalls Associated with Coordination Structures in Supply Chain Management: An Exploratory Case Study - Renu Agarwal; Preethi Subramani (International Journal of Supply Chain Management, 2013)
Supply chain management has recently received considerable attention with an aim to reduce production costs, manage risks, reduce delays, maximize profit, and improve the quality of products, with the result of increased competitiveness and profitability for all stakeholders. It is in this context that this paper investigates what coordination structures (focal, mediated or collaborative) are adopted by supply chains in an attempt to conduct integrative planning. We investigate what coordination structure is required by the focal firm to successfully manage supply chain activities. This paper draws on evidence from the extant literature and demonstrates the prevalence of the newly defined coordination structures in the manufacturing of complex products with a multitude supply chain based on findings from exploratory case studies. Potential opportunities and pitfalls associated with each of the coordination structures in regards to governance, supply risk, quality and supplier involvement practices are examined. Hypotheses are developed to help understand the impact of coordination structures on various supply chain activities. Previous studies have not considered the potential pitfalls and opportunities for the focal firm in choosing to adopt a particular coordination structure in the complex products manufacturing industry, which poses specific regulatory considerations. The two explanatory case studies also consider the perspective of tier 2 suppliers, which are not commonly considered in the supply chain literature. Moreover, this research is able to demonstrate that there is no such coordination structure as one size fits all, and instead illustrates that even different component supply chains in the same organisation can have different coordination structures.